Sensory characterization of the Ethiopian germplasm of Coffea arabica L. conserved in the Colombian Coffee Collection - Arias-Suárez, Juan Carlos; López-Monsalve, Luisa Fernanda; Medina-Rivera, Rubén Darío; Flórez-Ramos, Claudia Patricia (Frontiers in Sustainable Food Systems, 2025)
The sensory quality of coffee (Coffea arabica L.) has become increasingly important and is considered the best way to increase the competitiveness and profitability of the sector. Given the narrow genetic base cultivated, the use of its genetic resources conserved in germplasm banks is particularly relevant, especially for germplasm collected in Ethiopia, the country from which coffee originated and the center of its diversity of profiles. However, the potential benefits of using these resources is unknown. Therefore, the objective of this study was to characterize the sensory quality of the Ethiopian germplasm conserved in the Colombian Coffee Collection (CCC) to determine its variability and potential for use. The sensory qualities of drinks from 378 accessions of CCC were characterized. The results showed that 34% of the accessions evaluated presented sensory descriptors different from those of the traditional varieties. For the Global Impression attribute, the highest scores were associated with citrus, spice and floral notes. Additionally, prospecting rather than the area of origin of the germplasm influenced its sensory diversity, possibly due to the established objectives of the collection. The conserved germplasm exhibited important sensory variability, which is linked to rare descriptors in traditional varieties. Characterization activities of genetic resources, such as those conducted in this study, add value and serve as an initial step toward their application in breeding. The results obtained allow the selection of genotypes with distinct sensory profiles, which can be incorporated into genetic improvement programs aimed at developing future varieties with these attributes.